Voltage Flicker Mitigation Using STATCOM to Improve Power Quality of a Multi-Machine System: A Review - Pratibha Patel,; Pawan Pandey, (Journal of Power Electronics and Devices, 2023)
Modern power systems' transmission networks are under increasing strain as a result of rising demand and limitations on the construction of additional lines. The risk of losing stability after a disruption is one of the effects of such a strained system. The use of flexible ac transmission system (FACTS) devices in a transmission network has been found to significantly improve the utilisation of the network's current facilities without compromising the acceptable stability margin. To regulate voltage and power flow in electric power transmission networks, FACTS, including Static Synchronous Compensator (STATCOM), use the most recent power electronic switching device technology. By controlling the amount of reactive power absorbed or inoculate from the power supply, STATCOM modifies the voltage at its terminal. Reactive power is produced by STATCOM when the system voltage is low and absorbed by STATCOM when the system voltage is high. The suggested controllers are put into practice using the SIMULINK/MATLAB environment. The performance of PI-based controllers integrated with multi-machine systems is established to be superior to that of a conventional system.